<h2><u>Question :-</u></h2>
3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )
<h3>____________________</h3>
<h2><u>Solution :-</u></h2>
<h3><u>Given Information :-</u></h3>
- <u>Equation</u> ➢ 3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )
<h3><u>To Find :-</u></h3>
<h3><u>Calculation :-</u></h3>
⇒ 3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )
<em><u>Opening the brackets and multiplying the terms, We get, </u></em>
⇒ 3a - 3 + 31 - 11a = 8a + 12
⇒ -8a + 28 = 8a + 12
⇒ 8a + 8a = - 28 - 12
⇒ 16a = 40
<em><u>Transposing 16 to Right Hand Side, We get,</u></em>
⇒ a = ![\sf \frac{40}{16}](https://tex.z-dn.net/?f=%20%5Csf%20%5Cfrac%7B40%7D%7B16%7D%20)
⇒ a = ![\sf \frac{-2}{5}](https://tex.z-dn.net/?f=%20%5Csf%20%5Cfrac%7B-2%7D%7B5%7D%20)
<h3>____________________</h3>
<h2><u>Final Answer :-</u></h2>
- The value of 'a' is
![\bf \frac{-2}{5}](https://tex.z-dn.net/?f=%20%5Cbf%20%5Cfrac%7B-2%7D%7B5%7D%20)
<h3>____________________</h3>